Exercise Programme in Endometrial Cancer; Protocol of the Feasibility and Acceptability Survivorship Trial (EPEC-FAST). Issue 12 (16th December 2015) - Smits, Anke; Lopes, Alberto; Das, Nagindra; Bekkers, Ruud; Massuger, Leon; Galaal, Khadra
Abstract : Introduction: Obesity has been associated with impaired quality of life and poorer outcomes in endometrial cancer survivors. Lifestyle interventions promoting exercise and weight reduction have been proposed for survivorship care. However, studies evaluating exercise programmes for endometrial cancer survivors are lacking. Purpose: The objective of this study is to evaluate the feasibility of an individualised exercise intervention for endometrial cancer survivors to improve quality of life. Methods and analysis: This is a feasibility study in which women will undergo a 10-week exercise programme with a personal trainer. The study population comprises women with confirmed diagnosis of endometrial cancer, who have completed surgical treatment with curative intent, and are aged 18 years or older. The study will take place at the Royal Cornwall Hospital Trust, UK. Feasibility will be evaluated in terms of recruitment, adherence and compliance to the programme. Secondary outcomes are quality of life, psychological distress, fatigue, pain and complication rates. In addition, the acceptability of the programme will be assessed. Ethics and dissemination: Ethical approval was obtained through the Exeter NRES Committee. The study results will be used to optimise the intervention content, and may serve as the foundation for a larger definitive trial. Results will be disseminated through peer-review journals, congresses, relevant clinical groups and presented on the Trust's website. Trial registration number: NCT02367950; pre-results.